No interactions between heparin and atacicept, an antagonist of B cell survival cytokines. (15th October 2019) - Kowalczyk‐Quintas, Christine; Willen, Daniela; Willen, Laure; Golob, Michaela; Schuepbach‐Mallepell, Sonia; Peter, Benjamin; Eslami, Mahya; Vigolo, Michele; Broly, Hervé; Samy, Eileen; Yalkinoglu, Özkan; Schneider, Pascal
Abstract : Background and Purpose: The TNF family ligands, B cell activating factor of the TNF family (BAFF, also known as B lymphocyte stimulator, BLyS) and a proliferation‐inducing ligand (APRIL), share the transmembrane activator and calcium‐modulator and cyclophilin ligand (CAML)‐interactor (TACI) as one of their common receptors. Atacicept, a chimeric recombinant TACI/IgG1‐Fc fusion protein, inhibits both ligands. TACI and APRIL also bind to proteoglycans and to heparin that is structurally related to proteoglycans. It is unknown whether the portion of TACI contained in atacicept can bind directly to proteoglycans, or indirectly via APRIL, and whether this could interfere with the anti‐coagulant properties of heparin. Experimental Approach: Binding of atacicept and APRIL to proteoglycan‐positive cells was measured by FACS. Activities of heparin and atacicept were measured with activated factor Xa inhibition and cell‐based assays. Effects of heparin on circulating atacicept was monitored in mice. Key Results: Atacicept did not bind to proteoglycan‐positive cells, but when complexed to APRIL could do so indirectly via APRIL. Multimers of atacicept obtained after exposure to cysteine or BAFF 60‐mer bound directly to proteoglycans. Atacicept alone, or in complex with APRIL, or in a multimeric form did not interfere with heparin activity in vitro. Conversely, heparin did not influence inhibition of BAFF and APRIL by atacicept and did not change circulating levels of atacicept. Conclusions and Implications: Lack of detectable interference of APRIL‐bound or free atacicept on heparin activity makes it unlikely that atacicept at therapeutic doses will interfere with the function of heparin in vivo.